Онтологічний підхід до контролю знань в E-освіті - Тихонов, Юрій Леонтійович; Лахно, Валерій Анатолійович (НТУ "ХПІ", 2018)
У даній роботі пропонується онтологічний підхід до перевірки засвоєння знань, виявлення погано засвоюваних розділів навчального курсу. Це дозволяє на основі комп'ютерної онтології побудувати систему автоматизованого синтезу тестових завдань. Онтологічна БЗ забезпечує єдність міждисциплінарного простору знань. Підхід відрізняється застосуванням КО, що забезпечують систематизацію концептів, врахування їх взаємозв'язку. КО використовуються при автоматизації побудови тестів, що передбачають врахування відхилень сформованої в учня структури понять від реального онтографу ЕК, його структуризацію та розбивку на гілки, що відповідають певним фрагментам ЕК. Використовується ієрархічність онтографу (як сформованого в учня, так і реального).

There are a number of methods that determine the content, form, structure and procedure of the test. However, there is no toolkit based on a systematized and structured description of the objects of study. One of the successful approaches is ontological, where the knowledge of the subject domain is represented in a formalized form. The ontological aspects of the description include a range of issues ranging from structuring information to the linkages of objects. Among the features of the ontological description, we note the presence of levels of concepts and explicit indication of categories of higher order. In this paper we propose an ontological approach to the verification of knowledge acquisition, the discovery of poorly digestible sections of the training course. Computer ontology provides efficient machine processing of knowledge It allows to build on the basis of computer ontology a system of automated synthesis of test tasks. In contrast to the usual subjective approach, the ontological approach involves strict structuring of terms and concepts. Ontological knowledge base provides the unity of the interdisciplinary knowledge space. The approach is different in applying of computer ontologies, which ensures the systematization of concepts, taking into account their interconnection. Computer ontologies are used for automation of construction of tests, which involve taking into account the deviations of the pupil's structure of concepts from the real e-course ontograph, its structuring and division into branches corresponding to certain fragments of e-course. Used hierarchy ontograph (both formed in the student, and real). The algorithm of automated synthesis of tests is presented, which implements the above-mentioned ontological approach.
Ontological approach to knowledge control in E-learning
Keywords: комп'ютерна онтологія; онтограф; побудова тестів; ієрархічність; база знань; computer ontology; ontographer; construction of tests